Teori Permintaan Uang dan Konsep Uang Beredar dalam Ekonomi Islam - Aurelia Cahya Aini; Dea Marsa Amelia; Farhan Trisna Maulana; Sopia Icha Maharani4; Suci Hayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Money in the Islamic perspective is understood as a medium of exchange and unit of account that must have real value and be used in productive and fair economic activities. In the theory of demand for money, Islamic economics has three main approaches. The mainstream school adopts the general principles of conventional theory with adjustments to sharia values, such as the prohibition of usury and the requirement for transactions based on real assets. The Iqtisaduna school, emphasizes the relationship between the monetary system and the Islamic social structure based on the values of justice and individual responsibility. Meanwhile, the alternative school criticizes the fiat monetary system and offers a concept based on intrinsically valuable money such as the dinar and dirham. The three schools also provide different views on the concept of money in circulation, ranging from an adjusted conventional monetary policy approach to a model that rejects a paper money system without asset support. This study provides a clear conceptual mapping of the differences and contributions of each school to the development of the theory of demand for money and money circulation management in the Islamic economic system.